If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(x) = x * 2 + -6x + -15 Multiply F * x xF = x * 2 + -6x + -15 Reorder the terms for easier multiplication: xF = 2x + -6x + -15 Reorder the terms: xF = -15 + 2x + -6x Combine like terms: 2x + -6x = -4x xF = -15 + -4x Solving xF = -15 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 4x + xF = -15 + -4x + 4x Combine like terms: -4x + 4x = 0 4x + xF = -15 + 0 4x + xF = -15 Reorder the terms: 15 + 4x + xF = -15 + 15 Combine like terms: -15 + 15 = 0 15 + 4x + xF = 0 The solution to this equation could not be determined.
| 31=7c+-74 | | 15*15+9*9=x*x | | 4x+206=12+10 | | x-8+9-3=11 | | 6x-5-4x=17 | | Sin(x)=0.75 | | x=A+y+1 | | x-0.8=2.9 | | (12-x)+(x-14)=11 | | a=b-3x | | 0.125x+0.25(1500+x)=195 | | -7x+17y=-13 | | 106.2=9(m+3.6) | | 25-2y=3y+6 | | 12x=16x+14 | | 28375893475289ab+-988=-2+1+2b | | 27=.5(11x-1) | | 2x+19=97 | | x+29=14 | | 5Ib+3I=30 | | 6a+8=a+24 | | 7y+5=2y+13 | | 12d-2d=(d+3) | | 3381=49(p+10) | | 1092=26(p+10) | | K^4-4K^2-12=0 | | 11x+15y=358 | | (6x-1)-7=10-2x-2 | | 850=5(x+19) | | 3n-10=n+30 | | -7x+(-35)=28 | | 3-5x+2=20 |